Building Civil Society in Wartime: Opportunities and Challenges on the Example of the Military Crisis in Ukraine in 2014‒2023 - Kharuk, Daryna (Faces of War, 2025)
The article examines the development of diverse forms of activism within Ukrainian society and how citizens have been mobilised in response to oppressive authorities and war. Although the war has triggered a profound humanitarian and political crisis, it has simultaneously fostered an unprecedented strengthening of resilience within civil society. The first two decades following the declaration of Independence cannot be regarded as pivotal for civil society-building; however, the situation changed markedly after the events of the Euromaidan and the Revolution of Dignity. The scale of the Revolution of Dignity, together with the subsequent military actions and the sense of agency gained by citizens who catalysed far-reaching political and social change, exerted a considerable influence on those involved. As a result, some participants formed organisations that continue to operate to this day.Nevertheless, significant challenges persist in the functioning of Ukrainian civil society. These include the absence of long-term solutions to the ongoing humanitarian crisis, the discontinuity of reform processes, and the inability of the third sector to transform deeply entrenched corruption within state institutions. At present, many Ukrainian NGOs are undertaking functions that should properly fall within the remit of the state. This article therefore seeks to explore both the opportunities and the challenges facing civil society in Ukraine amid the ongoing war with Russia.